FREQUENCY AND CHARACTERISTICS OF MECKEL’S DIVERTICULUM IN TEN-YEAR BIOPSY MATERIAL OF THE INSITUTE OF PATHOLOGY - Mehmedović, Amin; Kotur, Milica; Trajković, Lazar (Medicinski podmladak, 2025)
Introduction: Meckel’s diverticulum is the most common congenital malformation of the gastrointestinal tract, which occurs due to incomplete obliteration of the omphalo-mesenteric duct. The prevalence of Meckel’s diverticulum in the general population is 0.3-2.9%, with a more frequent occurrence in men. It is mainly lined with typical ileal mucosa, although ectopic tissues may also be present. Complications due to the existence of Meckel’s diverticulum occur in about 4-16%. Aim: The aim of this work is to determine the macroscopic and histological characteristics of Meckel’s diverticulum, the frequency of the presence of ectopic tissue, the association with other anomalies and the presence of associated complications. Material and methods: This study includes the analysis of referrals for histopathological analysis and histological preparations of Meckel’s diverticulum of patients operated on in the period 2013-2022. Sixty samples of Meckel’s diverticulum were analyzed, with available data from histopathological referrals: frequency in different age groups, clinical manifestations, distribution by gender, length of diverticulum, frequency of ectopic tissue occurrence, frequency and type of complications. Results: Meckel’s diverticulum was found 3.6 times more often in boys. The median age of patients at the time of surgery was 9.5 years (0.00-17.5). In 6 patients (10%), the presence of associated anomalies and/or significant diseases was determined. In 23 patients (38.33%), the following clinical symptoms were found: abdominal pain accompanied by nausea, vomiting and constipation. In 10 (16.67%) patients there was melena, or fresh blood was observed in the stool. Heterotopic tissue was observed in 30 patients (50%). Complications of Meckel’s diverticulum were observed in 31 patients (51.67%). No statistically significant association was found between the length of Meckel’s diverticulum and the presence of heterotopic tissue. Conclusion: Although Meckel’s diverticulum is a rare anomaly, the frequency of complications is relatively high, so adequate monitoring of patients is of great importance.